An Investigation into Linguistic Features of Metaphor use in English and Vietnamese Advertisements - Huỳnh Trung Ngữ (2011)
The thesis aims at investigating conceptual metaphors in English and Vietnamese advertisements, namely through comparison and bilateral contrastiveness, and the author points out the similarities and differences in …